A new species of Doryctobracon Enderlein (Hymenoptera, Braconidae) parasitizing larvae of Anastrepha Schiner (Diptera, Tephritidae), with illustrated key to species of Doryctobracon that parasitize fruit-infesting tephritids in Brazil - Marinho, Cláudia F.; de Souza-Filho, Miguel F.; Raga, Adalton; Santos, Wyratan Da S.; Zucchi, Roberto A. (Zootaxa, 2021)
Doryctobracon maculatus Marinho, a new species of Braconidae (Opiinae) collected in the municipalities of Piracicaba and São Roque, state of São Paulo, Brazil, is described and illustrated. This new species is placed in group of species with areolate propodeum, but is easily distinguished from other species of this group, and other members of the genus by the noticeable black to dark-brown spots on the head, mesosoma and metasoma. This new species was reared in larvae of Anastrepha pseudoparallela (Diptera, Tephritidae) in passion fruits, Passiflora alata Curtis (Passifloraceae). An illustrated key to species of Doryctobracon recorded in Brazil is presented.